Polar flock in the presence of random quenched rotators - Das, Rakesh; Kumar, Manoranjan; Mishra, Shradha (American Physical Society, 2018)
We study a collection of polar self-propelled particles (SPPs) on a two-dimensional substrate in the presence of random quenched rotators. These rotators act like obstacles which rotate the orientation of the SPPs by an angle determined by their intrinsic orientations. In the zero self-propulsion limit, our model reduces to the equilibrium XY model with quenched disorder, while for the clean system, it is similar to the Vicsek model for polar flock. We note that a small amount of the quenched rotators destroys the long-range order usually noted in the clean SPPs. The system shows a quasi-long range order state upto some moderate density of the rotators. On further increment in the density of rotators, the system shows a continuous transition from the quasi-long-range order to disorder state at some critical density of rotators. Our linearized hydrodynamic calculation predicts anisotropic higher order fluctuation in two-point structure factors for density and velocity fields of the SPPs. We argue that nonlinear terms probably suppress this fluctuation such that no long-range order but only a quasi-long-range order prevails in the system. © 2018 American Physical Society.
Keywords: Velocity; Continuous transitions; Critical density; Hydrodynamic calculation; Long range orders; Quasi long range orders; Quenched disorder; Self propulsion; Self-propelled particles; Surface plasmon resonance